Greening Africa? Technologies, endowments and the latecomer effect. - Collier, P; Venables, A (CSAE (University of Oxford), 2012)
Africa is well endowed with potential for hydro and solar power, but its other endowments – shortages of capital, skills, and governance capacity – make most of the green options relatively expensive, while its abundance of hydro-carbons makes fossil fuels relatively cheap. Current power shortages make expansion of power capacity a priority. Africa’s endowments, and the consequent scarcities and relative prices, are not immutable and can be changed to bring opportunity costs in Africa closer to those in the rest of the world. The international community can support by increasing Africa’s supply of the scarce factors of capital, skills, and governance.